Sagittal otolith-based age estimation of a candidate aquaculture species, bigeye scad (Selar crumenophthalmus) from the Southern Sibuyan sea, Philippines. - Sandig, Nancy D.
Bigeye scad, Selar crumenophthalmus (Bloch, 1793), is a small pelagic schooling marine species belonging to the family Carangidae with a circumtropical distribution. Sustainable utilization of fish stocks involve the determination of fish age which is vital in gathering information on recruitment, lifespan, mortality, and changes in the fishery. Fish age is found as permanent imprints or increments on some hard body components of fishes such as the scales, spines, rays, otoliths. In most bony fishes, the sagittae is the largest pair of otoliths and has been used to measure the age and growth of fish. This study aims to estimate the age of bigeye scad from the Southern Sibuyan Sea through otolith-based analysis. Specifically, this study aims to (a) examine sagittal otolith daily growth increment at varying class sizes and (b) assess the precision of the otolith-based age estimation. The right sagittal otoliths were polished using 400 to 1000-grit sandpaper and TEEDA DC Grinder Set and otolith rings were counted using the ImageJ application. Reading precision was analyzed using CV with ≤ 5% acceptable level.The results showed that the correlation between fish length and otolith growth increment formation was significant (p <0.001). As the fish grows in length, the number of otolith growth increments increases. It was also revealed that otolith dimensions-weight and length-have a direct correlation to fish length and weight using Pearson Correlation Coefficient (p <0.001). However, significant imprecision was found in the growth increment readings across the sample with CV values way higher than the acceptable level.